Abnormal Ca2+ homeostasis, atrial arrhythmogenesis, and sinus node dysfunction in murine hearts modeling RyR2 modification - Zhang, Yanmin; Matthews, Gareth D.; Lei, Ming; Huang, Christopher L. (Frontiers in Physiology, 2013)
RyR2 mutations are implicated in catecholaminergic polymorphic ventricular tachycardia thought to result from altered myocyte Ca2+ homeostasis reflecting inappropriate ‘leakiness’ of RyR2-Ca2+ release channels arising from increases in their basal activity, alterations in their phosphorylation, or defective interactions with other molecules or ions. The latter include calstabin, calsequestrin-2, Mg2+, and extraluminal or intraluminal Ca2+. Recent clinical studies additionally associate RyR2 abnormalities with atrial arrhythmias including atrial tachycardia, fibrillation and standstill, and sinus node dysfunction. Some RyR2 mutations associated with CPVT in mouse models also show such arrhythmias that similarly correlate with altered Ca2+ homeostasis. Some examples show evidence for increased Ca2+/calmodulin-dependent protein kinase II phosphorylation of RyR2. A homozygotic RyR2-P2328S variant demonstrates potential arrhythmic substrate resulting from reduced conduction velocity in addition to delayed afterdepolarizations and ectopic action potential firing. Finally, one model with an increased RyR2 activity in the sino-atrial node shows decreased automaticity in the presence of Ca2+-dependent decreases in ICa,L and diastolic sarcoplasmic reticular Ca2+ depletion.